Immunogenicity and safety of 3-dose primary vaccination with combined DTPa-HBV-IPV/Hib vaccine in Canadian Aboriginal and non-Aboriginal infants. Issue 16 (15th April 2015) - Scheifele, David W.; Ferguson, Murdo; Predy, Gerald; Dawar, Meena; Assudani, Deepak; Kuriyakose, Sherine; Van Der Meeren, Olivier; Han, Htay-Htay
Highlights: These are the first available data on immune responses of Canadian Aboriginal infants to routine vaccines. Responses of Aboriginal and non-Aboriginal infants were compared after 3 doses of a hexavalent combination vaccine. Responses to H. influenzae b and hepatitis B components were at least as high in Aboriginal as in non-Aboriginal infants. Abstract: This study compared immune responses of healthy Aboriginal and non-Aboriginal infants to Haemophilus influenzae type b (Hib) and hepatitis B virus (HBV) components of a DTaP-HBV-IPV/Hib combination vaccine, 1 month after completing dosing at 2, 4 and 6 months of age. Of 112 infants enrolled in each group, 94 Aboriginal and 107 non-Aboriginal infants qualified for the immunogenicity analysis. Anti-PRP concentrations exceeded the protective minimum (≥0.15 μg/ml) in ≥97% of infants in both groups but geometric mean concentrations (GMCs) were higher in Aboriginal infants (6.12 μg/ml versus 3.51 μg/ml). All subjects were seroprotected (anti-HBs ≥10 mIU/mL) against HBV, with groups having similar GMCs (1797.9 versus 1544.4 mIU/mL, Aboriginal versus non-Aboriginal, respectively). No safety concerns were identified. We conclude that 3-dose primary vaccination with DTaP-HBV-IPV/Hib combination vaccine elicited immune responses to Hib and HBV components that were at least as high in Aboriginal as in non-Aboriginal Canadian infants. Clinical Trial RegistrationNCT00753649 .